Flow Cytometry Instrumentation – An Overview. Issue 1 (16th November 2018) - Büscher, Martin
Abstract: The term flow cytometry, used since the seventies, describes a technology employed mainly in biology and medicine to measure and classify suspended particles, e.g., cells or microspheres. Measurable cell parameters include: geometric properties, such as cell size (diameter, surface area, volume); physiological properties (membrane potential, integrity, vitality); and quantities of DNA, RNA, cytokines, surface antigens, nuclear antigens, enzymes, and proteins. © 2018 by John Wiley & Sons, Inc.